If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3y = -21 Solving 6x + 3y = -21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 6x + 3y + -3y = -21 + -3y Combine like terms: 3y + -3y = 0 6x + 0 = -21 + -3y 6x = -21 + -3y Divide each side by '6'. x = -3.5 + -0.5y Simplifying x = -3.5 + -0.5y
| 27x=15x+70200+4x-23400+59400 | | (5xy*y*y)*(-2x*-2x*-2x*-2x*y*y*y*y*y)= | | -2-13.8n=8n(6n+1) | | 2+7x=16+3x | | 2n^2+8=2n+3 | | 2(x+5)+5x=7x-10 | | x/12=8/11 | | 1=(7x+14) | | 4-3(ln)x=-8 | | 0.028= | | (4/9)*(5/9) | | x^4+4x^3-21x=0 | | 100000000*log(sub)2(1+3)= | | 3x-4-2x=4 | | log(sub)2(1+3)= | | 2m(1+x^2)-(1+m^2)(x+m)=0 | | 3(3y+4)=4y+27 | | -2x+10=4-12x-1+14 | | -5y=-y-32 | | f(x)=1/2x-3 | | -4x+10+2x=20 | | 5a-b+3a+2b= | | 7t^2-40t+48=0 | | 234-x=132 | | 15w+20=10w-45 | | 9b/3b-6/3b | | x^2+6x=-y^2-18y-41 | | [4/x-3]-[(4-3x)/4] | | 35-x=26 | | 3(a-4)-12=5(a+1) | | 5x-3x^2y+2yz^2=0 | | 2x+5*5.09=35 |